Post Mergers And Acquisitions And Its Effect On Organizational Behaviour - A Study With Reference To Manufacturing Companies In India (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Objective Of This Research Is To Examine The Effect Of Merger & Acquisitions On Organizational Behaviour Of Manufacturing Firms. The Research Was Done On 5 Selected Companies That Have Undergone Consolidation In Recent Time. The Independent Variables Of The Study Are Policy Change, Structural Change And Process Change Meanwhile The Dependent Variables Are Reaction To Change And Overall Performance. The Study Employed Multiple Regression And Correlation Analysis For Measuring The Impact Of M&A On Organization And The Result Illustrated That The Variable Is Positively Correlated To Overall Performance.